2022
DOI: 10.3390/photonics9080582
|View full text |Cite
|
Sign up to set email alerts
|

Blind Restoration of Images Distorted by Atmospheric Turbulence Based on Deep Transfer Learning

Abstract: Removing space-time varying blur and geometric distortions simultaneously from an image is a challenging task. Recent methods (including physical-based methods or learning-based methods) commonly default the turbulence-degraded operator as a fixed convolution operator. Obviously, the assumption does not hold in practice. According to the situation that the real turbulence distorted operator has double uncertainty in space and time dimensions, this paper reports a novel deep transfer learning (DTL) network fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Deep convolutional neural networks (CNNs) are a new type of network and have the ability to automatically effectively learn the nonlinear relationship between input and output [8][9][10]. Recent studies have shown that deep convolutional neural networks (CNNs) are widely used in image restoration tasks [11][12][13][14][15] in computer vision. For instance, Liu et al [16] proposed a novel approach that merged multilevel image restoration with the pix2pix generative adversarial network architecture within the lensless imaging sphere, which greatly improved image recovery quality in lensless systems.…”
Section: Introductionmentioning
confidence: 99%
“…Deep convolutional neural networks (CNNs) are a new type of network and have the ability to automatically effectively learn the nonlinear relationship between input and output [8][9][10]. Recent studies have shown that deep convolutional neural networks (CNNs) are widely used in image restoration tasks [11][12][13][14][15] in computer vision. For instance, Liu et al [16] proposed a novel approach that merged multilevel image restoration with the pix2pix generative adversarial network architecture within the lensless imaging sphere, which greatly improved image recovery quality in lensless systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, detecting the presence of a filtering function due to atmospheric scattering is the focus, rather than defining the precise form of the function. The concept of atmospheric filtering is mentioned by Guo et al (2022) who investigated neural network-based restoration of images distorted by atmospheric turbulence. We do not need to go so far as to restore images blurred by clouds in a large multi-year database of auroral imagery, but we can leverage the effect of clouds on keograms to determine their presence.…”
mentioning
confidence: 99%